IOFlow: A Software-Defined Storage Architecture - Thereska, Eno; Ballani, Hitesh; O'Shea, Greg; Karagiannis, Thomas; Rowstron, Ant; Talepy, Tom; Black, Richard; Zhu, Timothy (SOSP'13: The 24th ACM Symposium on Operating Systems Principles, 2013)
In data centers, the IO path to storage is long and complex. It comprises many layers or “stages” with opaque interfaces between them. This makes it hard to enforce end-to-end policies that dictate a storage IO flow’s performance (e.g., guarantee a tenant’s IO bandwidth) and routing (e.g., route an untrusted VM’s traffic through a sanitization middlebox). These policies require IO differentiation along the flow path and global visibility at the control plane. We design IOFlow, an architecture that uses a logically centralized control plane to enable high-level flow policies. IOFlow adds a queuing abstraction at data-plane stages and exposes this to the controller. The controller can then translate policies into queuing rules at individual stages. It can also choose among multiple stages for policy enforcement. We have built the queue and control functionality at two key OS stages– the storage drivers in the hypervisor and the storage server. IOFlow does not require application or VM changes, a key strength for deployability. We have deployed a prototype across a small testbed with a 40 Gbps network and storage devices. We have built control applications that enable a broad class of multipoint flow policies that are hard to achieve today.
SOSP’13, Nov. 3–6, 2013, Farmington, PA, USA. ACM 978-1-4503-2388-8/13/11. http://dx.doi.org/10.1145/2517349.2522723